SWITCH 1/DYAD is a WINGS APART-LIKE antagonist that maintains sister chromatid cohesion in meiosis - Chao Yang (Nature Portfolio, 2019)
During cell division, Soronin antagonises WAPL to prevent premature loss of sister chromatid cohesion. Here the authors show that, despite a lack of sequence similarity, the Arabidopsis SWI1 protein functions as a novel Soronin-like WAPL antagonist, suggesting convergent evolution with animals.